Regulation of Precarious Employment in Single-Industry Towns - Bobkov, Vyacheslav Nikolaevich; Odegov, Yuri Gennadievich; Garnov, Andrei Petrovich (Economy of Regions, 2020)
The article discusses how to ensure stable employment in single-industry towns. The Russian labour market has changed significantly due to the transition to a digital society, which transforms both communication technologies and the motivation of labour behaviour. A widespread introduction of non-standard forms of employment has both positive effects and negative risks. To minimize such risks, it is necessary to find mechanisms to increase the economic and social security of standard and non-standard employees. For examining precarious employment, we used studies of foreign and Russian authors, focusing on the characteristics of employment in single-industry towns. Despite the variety of conditions, which are necessary for the socioeconomic development of single-industry towns and forms of employment, we hypothesise that it is possible to develop a unified approach, combining standard and non-standard employment. We demonstrated that the situation, on the labour market in single-industry towns remains tense. In such towns, the number of employed population is decreasing, while their working and employment conditions are getting worse. Thus, we suggest developing the policy of employment management in single-industry towns using a system of measures aimed at forming balanced standard and non-standard employment. At the regional level, the research results can be applied for elaborating proposals for reducing tension in labour markets of single-industry towns.